Histological and Histochemical Studies on the Junctions of Small and Large Intestine of Broiler Chickens - Rajpoot, Neeraj Singh (Indian Journal of Veterinary Anatomy, 2020)
The intestinal junctions of broiler chickens of different age groups were studied. The duodeno-jejunal, jejuno-ileal and ileo-caecal junctions were lined by simple columnar epithelium having varying numbers of chief, goblet and endocrine cells. The number of goblet and endocrine cells increased and decreased, respectively cranio-caudally in different junctions. The goblet cells and the intestinal glands of different junctions showed a strong reaction for acidic mucopolysaccharides by PAS Alcian blue and colloidal iron methods. An Alcianophilic reaction in the secretions indicated presence of hyaluronic acid, weakly sulfated mucopolysaccharides and sialomucins. Mucins were also strongly positive whereas the glycogen reaction was moderate. The histologicalfeatures were almost identical in different intestinal junctions except some qualitative differences.